THE THEORY OF CONSTRAINTS AND ITS IMPORTANCE IN MODERN MANAGEMENT: AN ANALYTICAL REVIEW BASED ON “THE GOAL” - Maraimova K. Sh. (PhD); Chinmirzayev Sh. S.; Sobirjonov Sh. B. (Western European Studies, 2025)
This paper summaries the Theory of Constraints (TOC) presented in the book the Goal of Eliyahu Goldratt. It applies the stories of the book and compares them with the current business patterns of doing things. Like a school report (IMRAD), the review discusses the main concepts, throughput, inventory, and operating expense, and addresses such tools as the Drum-Buffer-Rope (DBR) model. The article makes the comparisons to reveal that TOC remains valuable with some issues highlighted in high-speed contemporary settings. It concludes that by 20-50 percent in a factory and service facilities, TOC has been shown to increase efficiency, where there are examples of existing hospitals and supply chains. It teaches managers to identify constraints at an early stage and look after buffers. The review combines theory of The Goal and tips of the world and demonstrates how TOC can be used to continue improving things.
Keywords: identify; inventory; supply chains